Students’ perception of informal interaction spaces of Faculty Buildings in Federal University of Technology, Minna, Nigeria - Adedayo, Olatunde Folaranmi; Oyetola, Stephen Ayodele; Anunobi, Anthony Ikechukwu; Adebayo, Oluwatoyin Abiodun (Penerbit Universiti Kebangsaan Malaysia, 2018)
Faculty buildings have often been considered as a place for formal activities in terms of learning and teaching by both lecturers and students. Emphasis has always been placed on the formal learning environment by the management of such institutions and also the accrediting bodies of such institutions. The designs of such faculties have also reflected the same emphasis with attention being placed on the formal learning spaces and offices for staff. The informal spaces often found in faculty buildings are treated as secondary with such spaces often evolving as the uses of the building continues. They are usually unplanned places which are created by the students as their needs arise. The aim of this study is to examine how effective these informal interaction spaces have served the students. Four out of Eight faculties were purposively selected from the study area based on the student population, while the students were randomly selected. The data obtained were analysed using descriptive statistics and the results were presented in tables, charts and plates. It was observed that the students were dissatisfied with the designated informal interaction spaces provided by the designs of the buildings, it also showed that informal interaction spaces evolved as solution for waiting periods outside lecture rooms. The study concludes that there was need to design faculty buildings that had lecture rooms linked to open spaces and overflow areas aside from corridors that were predominant in the study area.